2007
DOI: 10.1152/ajprenal.00474.2006
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular calcium-sensing receptor is functionally expressed in human artery

Abstract: Accelerated medial calcification is a major cause of premature cardiovascular mortality in patients with chronic kidney disease (CKD). Evidence suggests that extracellular concentration of Ca2+ and vascular smooth muscle cells may play a pivotal role in the pathogenesis of vascular calcification. The calcium-sensing receptor (CaSR) is a G protein-coupled receptor that is expressed in a range of tissues, but characterization of its expression and function in the cardiovascular system is limited. Here we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 40 publications
7
103
1
1
Order By: Relevance
“…Recent reports clearly point to a role for the CaSR as a regulator of early development and as a guardian of the homeostatic balance between proliferation and differentiation in adults [19,68,70,71,73,75,89,92]. The identification of CaSR mutations that cause FHH and hypocalcemia [93][94][95][96][97][98], and the recent discoveries implicating the dysregulation of CaSR signaling in many other diseases [99,[113][114][115][119][120][121][122][123][124], position the CaSR as a broad therapeutic target. Adverse side-effects will likely be a challenging issue in the putative use of CaSR-modulating agents for the treatment of such a broad range of tissuespecific diseases; therefore, future studies should focus on the development of CaSR-modulating drugs with a higher selectivity for the CaSR and specificity for the tissue of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports clearly point to a role for the CaSR as a regulator of early development and as a guardian of the homeostatic balance between proliferation and differentiation in adults [19,68,70,71,73,75,89,92]. The identification of CaSR mutations that cause FHH and hypocalcemia [93][94][95][96][97][98], and the recent discoveries implicating the dysregulation of CaSR signaling in many other diseases [99,[113][114][115][119][120][121][122][123][124], position the CaSR as a broad therapeutic target. Adverse side-effects will likely be a challenging issue in the putative use of CaSR-modulating agents for the treatment of such a broad range of tissuespecific diseases; therefore, future studies should focus on the development of CaSR-modulating drugs with a higher selectivity for the CaSR and specificity for the tissue of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular calcification is an active, regulated process similar to that of osteogenesis in bone. During this process, loss of CaSR expression in vascular smooth muscle cells leads to the acquisition of an osteoblast-like phenotype and contributes to the generation of calcified nodules [119][120][121][122][123]. Koleganova and colleagues demonstrated, using an in vivo rat model for interstitial fibrosis and microvascular disease of the heart in uremia, that this transdifferentiation could be significantly delayed by administration of the calcimimetic R-568, suggesting the involvement of the CaSR in this process [124].…”
Section: Atherosclerosismentioning
confidence: 99%
“…Compared with normal individuals, the expression of this Ca 2ϩ -sensing receptor is downregulated in VSMCs from patients with CKD. 71 Thus, the extracellular Ca 2ϩ and Ca 2ϩ receptor axis may have a role in the progression of vascular calcification.…”
Section: Elastin Degradationmentioning
confidence: 99%
“…At present it is not known whether changes in dietary calcium affect blood pressure through the action of the CaR on endothelial and smooth vascular cells of human arteries (Molostvov et al, 2007). Alternatively, activation of the renal CaR leading to enhanced prostaglandin E 2 synthesis and natriuresis with subsequent reduction in plasma volume, may account for the blood pressure-lowering effect of elevated extracellular calcium (Wang et al, 2001).…”
Section: Vitamin D Calcium and Chronic Diseases M Peterlik And Hs Crossmentioning
confidence: 99%
“…Molostvov et al (2007) suggested that arterial calcification, which is a major cause of premature cardiovascular mortality, could be the result of CaR activation. Thus, one cannot exclude that calcium supplementation may cause adverse vascular events that compromise, at least in part, its beneficial action on cardiovascular risk.…”
Section: Cardiovascular Diseasementioning
confidence: 99%